2017
DOI: 10.1136/bcr-2017-220994
|View full text |Cite
|
Sign up to set email alerts
|

Reversible central neural hyperexcitability: an electroencephalographic clue to hypocalcaemia

Abstract: A 23-year-old male patient presented with cognitive decline and seizures. Examination revealed Chvostek's and Trousseau's signs. Investigations revealed hypocalcaemia, hyperphosphatemia and normal intact parathyroid hormone levels. Imaging showed calcifications in bilateral basal ganglia, thalamus and dentate nuclei. Interictal electroencephalogram showed theta range slowing of background activity and bilateral temporo-occipital, irregular, sharp and slow wave discharges, which accentuated during hyperventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Several studies have shown hypocalcemia to be associated with SAE ( 40 42 ), and our present study revealed that it is an independent risk factor. EEG in hypocalcemia is characterized by generalized theta/delta range background slowing and focal or generalized spike and wave discharges, suggesting central neural hyperexcitability ( 43 ). It is further speculated that in sepsis with hypocalcemia, there is both increased neuromuscular excitability, which causes convulsions, as well as reduced cerebral blood flow and abnormal nerve conduction function, which causes cerebral ischemia-hypoxia and finally promotes the occurrence of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown hypocalcemia to be associated with SAE ( 40 42 ), and our present study revealed that it is an independent risk factor. EEG in hypocalcemia is characterized by generalized theta/delta range background slowing and focal or generalized spike and wave discharges, suggesting central neural hyperexcitability ( 43 ). It is further speculated that in sepsis with hypocalcemia, there is both increased neuromuscular excitability, which causes convulsions, as well as reduced cerebral blood flow and abnormal nerve conduction function, which causes cerebral ischemia-hypoxia and finally promotes the occurrence of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…The electroencephalogram in hypocalcemic seizures may present focal spikes and rhythmic, high-voltage discharges over the frontocentral region that rapidly generalize [ 12 ]. These EEG abnormalities emerge as a result of neuronal hyperexcitability and can be entirely reversible following the amelioration of serum calcium concentration [ 13 ]. A study conducted by R. Vargas et al declared the L125P mutant is the most potent GoF mutation, and it is associated with a Bartter-like syndrome (renal sodium chloride depletion that is accompanied by secondary hyperaldosteronism and hypokalemia) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%